P58 Head Injury CT scan: measuring up to NICE guidelines. (8th April 2021) - Ghalab, Ahmed; Tariq, Munim; Akram, Rahim; Ikwuagwu, Allen; Ghalab, Ahmed
Abstract: Introduction: Head injury is the most common cause of death and disability in individuals between 1-40 years in the UK, with roughly 200, 000 annual admissions. The aim is to evaluate how effectively CT scans following a head injury are being performed with reference to NICE guidelines 1-hour criteria1 as patient's prognosis could potentially be improved with early detection. Standards: 100% of patients should be scanned within 1 hour of risk factors being identified. 100% of provisional radiology reports on CT-heads should be completed within 1 hour of the scan being performed: All requests from emergency department must have clear documentation of head injury risk factors justifying scan Methods: retrospective audit collecting data from 01/01/2020 to 14/01/2020 for 1st cycle and from 14/10/2020 to 30/10/2020 for 2nd cycle. Requests were found on the electronic request system (ICE) to assess clinical information provided by ED clinicians only taking into account those scans following a head injury according to NICE guidelines. Results First cycle: 100 scans were examined with only 36% meeting criteria for 1 hr scan. Only 19 (52%) of those patients had received all 3 measures of the standard. In total 8 patients had positive findings with only 4 patients getting scan and report on time. Second cycle: 100 scans were examined with 45% meeting criteria for 1 hr scan. 37 (83%) had received all 3 measures of the standard. In total 13 patients had positive findings with 11 patients getting scan and report on time. Conclusion: About only half of the patients presenting with the risk factors got their scan done in line with NICE guidelines. Following change of ICE to include criteria patients were better categorized, eliminating any unnecessary scans, reducing waiting times and cost, improving patient flow in ED and all scans are now justifiable according to criteria. References: 1-National Institute for Health and Clinical Excellence. CG176. Head Injury: assessment and early management. London. January 2014. https://www.nice.org.uk/guidance/cg176: 2-irefer . The Royal College of Radiologists. Making the best use of clinical radiology services 8th edition. 2017 https://www.rcr.ac.uk/sso/irefer/v8: 3 -https://www.rcr.ac.uk/audit/compliance-nice-guidelines-2014-traumatic-head-injury-regard-ct